Coronary artery bypass grafting with concomitant resection for carcinoma of lung - Zhang, Yangyang (Editorial Department of Journal of Biomedical Research, 2010)
A 69-year-old woman with angina had a lesion in the left lower lobe on chest film. Angiography revealed coronary artery disease in three vessels. Combined off pump coronary artery bypass grafting (CABG) and left lower lobectomy were performed through median sternotomy. This approach avoids complications due to staged operations and cardiopulmonary bypass (CPB). This report shows that simultaneous off pump CABG and pulmonary operations can be performed safely in patients with coronary artery disease (CAD) associated with lung cancer.